2017
DOI: 10.1200/jco.2017.35.15_suppl.557
|View full text |Cite
|
Sign up to set email alerts
|

Primary operation in synchroneous metastasized invasive breast cancer patients: First oncologic outcomes of the prospective randomized phase III ABCSG 28 POSYTIVE trial.

Abstract: 557 Background: The ABCSG 28 Posytive trial compared primary surgery versus primary systemic therapy without surgery in stage IV breast cancer patients. The primary aim was to investigate whether immediate resection of the primary tumor followed by standard systemic therapy improves median survival compared with no surgical resection (NCT01015625). The trial had to be stopped early due insufficient recruitment. Methods: Untreated stage IV breast cancer patients with the primary in situ were randomly assigned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
111
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(114 citation statements)
references
References 0 publications
3
111
0
Order By: Relevance
“…5 The recent Austrian ABCSG-28 POSITIVE study did not mention relevant local problems. 6 Therefore, in the Discussion of the Turkish study, the authors mentioned that the role of local resection in the control of local symptoms was an unsolved issue worthy of examination and research. Therefore, in our retrospective study, we proposed the research term ''local progress/recurrence of symptoms'' (LPRS) to represent the local symptoms caused by tumor progression/recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 The recent Austrian ABCSG-28 POSITIVE study did not mention relevant local problems. 6 Therefore, in the Discussion of the Turkish study, the authors mentioned that the role of local resection in the control of local symptoms was an unsolved issue worthy of examination and research. Therefore, in our retrospective study, we proposed the research term ''local progress/recurrence of symptoms'' (LPRS) to represent the local symptoms caused by tumor progression/recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several prospective studies have focused on whether local resection can improve prognosis of patients diagnosed with de novo stage IV BC, [4][5][6] but the final results have not been consistent, and other retrospective analyses have also yielded controversial results in answer to this question. [7][8][9][10] Aside from survival, no studies have focused on the effect of surgery on local symptoms caused by tumor progression/recurrence.…”
mentioning
confidence: 99%
“…However, a limited number of prospective randomized controlled clinical trials have produced con icting results. A recently published study in Austria indicates no OS bene t of surgical resection of the primary tumor in primary stage IV breast cancer [25]. No credible conclusions can be drawn from these studies because they are small and non-randomized, and all of them have cohorts selected from a single institution.…”
Section: Discussionmentioning
confidence: 99%
“…However, this trial was ended early because of poor accrual of patients, raising questions regarding the power of its statistical analysis. 10 One notable recent study of surgery for de novo stage 4 breast cancer is the MF07-01 trial sponsored by the Turkish Federation of the National Societies for Breast Disease. 11 In this study, the last statistical analysis in a median followup period of 40 months showed results that differed from those of the previous 36-month follow-up period, in which no difference in survival was noted between the surgery and no-surgery groups.…”
mentioning
confidence: 99%